Pengaruh Jenis Minyak Terhadap Sifat Fisik Sabun Mandi Cair - Febrina Nugrahini; Nining Sugihartini; Laela Hayu Nurani (Jurnal Surya Medika (JSM), 2020)
Soap is obtained from the saponification reaction that occurs between oil and alkaline solution. Various kinds of oils used in soap making also affect the quality of soap. The purpose of this study is to determine the effect of oil type on the physical properties of liquid bath soap. This research was divided into 3 groups, coconut oil group (A), VCO oil group (B), and olive oil group (C). Liquid bath soap obtained from each type of oil is tested based on SNI provisions including a soap quality test (oil characteristics test, organoleptic test, pH test, specific gravity, total plate count), viscosity test, and antioxidant test. Liquid bath soap of the three types of oil has the same shape, color, and odor. Coconut liquid soap, VCO, and olives respectively have a pH value of 6.64; 6.9; 6.52. (P = 0,000) Specific weight 1.0511; 1.0427; 1.0425. Viscosity 558cps; 686; 420. (p = 0.003) IC50 3547.36; 4523.46; 3542.02. (p = 0.035). Bath soaps that best meet SNI requirements are those made with olive oil.